Assessing the Functional Redundancy between P-gp and BCRP in Controlling the Brain Distribution and Biliary Excretion of Dual Substrates with PET Imaging in Mice - Irene Hernández-Lozano; Severin Mairinger; Alexander Traxl; Michael Sauberer; Thomas Filip; Johann Stanek; Claudia Kuntner; Thomas Wanek; Oliver Langer (MDPI AG, 2021)
P-glycoprotein (P-gp) and breast cancer resistance protein (BCRP) are co-localized at the blood-brain barrier, where they display functional redundancy to restrict the brain distribution of dual P-gp/BCRP substrate drugs. We used positron emission tomography (PET) with the metabolically stable P-gp/BCRP substrates [11C]tariquidar, [11C]erlotinib, and [11C]elacridar to assess whether a similar functional redundancy as at the BBB exists in the liver, where both transporters mediate the biliary excretion of drugs. Wild-type, Abcb1a/b(−/−), Abcg2(−/−), and Abcb1a/b(−/−)Abcg2(−/−) mice underwent dynamic whole-body PET scans after i.v. injection of either [11C]tariquidar, [11C]erlotinib, or [11C]elacridar. Brain uptake of all three radiotracers was markedly higher in Abcb1a/b(−/−)Abcg2(−/−) mice than in wild-type mice, while only moderately changed in Abcb1a/b(−/−) and Abcg2(−/−) mice. The transfer of radioactivity from liver to excreted bile was significantly lower in Abcb1a/b(−/−)Abcg2(−/−) mice and almost unchanged in Abcb1a/b(−/−) and Abcg2(−/−) mice (with the exception of [11C]erlotinib, for which biliary excretion was also significantly reduced in Abcg2(−/−) mice). Our data provide evidence for redundancy between P-gp and BCRP in controlling both the brain distribution and biliary excretion of dual P-gp/BCRP substrates and highlight the utility of PET as an upcoming tool to assess the effect of transporters on drug disposition at a whole-body level.